Peningkatan Keterampilan Komunikasi Bisnis dalam Pelayanan Jasa untuk Dunia Usaha pada Siswa SMKN 3 Pontianak - Yohanes Sriwomatu; Uray, Andrey Indra Maulana (Jurnal Pengabdian Kepada Masyarakat, 2025)
Business communication is an essential skill in the worl of work, especially in the field of services that require direct interaction with customers. SMK students as prospective workers need to be equipped with an understanding and practice of effective business communication to improve service quality. This activity aims to improve the understanding and skills of SMKN 3 Pontianak students in applying business communication to support quality service. The methods used in this service activity are interactive counseling and case study-based training as well as service practice simulations. Data collection was done through direct observation and questionnaires before and after the activity to measure the improvement od students understanding. The data were analyzed descriptively to see the effectiveness of the program provided. The results of this activity showed significant improvement in business communication concepts and their application in real service situations. Students also showed better ability in conveying information professionally, being polite and handling customer complaints constructively.